2014
DOI: 10.1002/jcc.23716
|View full text |Cite
|
Sign up to set email alerts
|

The CHARMM–TURBOMOLE interface for efficient and accurate QM/MM molecular dynamics, free energies, and excited state properties

Abstract: The quantum mechanical (QM)/molecular mechanical (MM) interface between Chemistry at HARvard Molecular Mechanics (CHARMM) and TURBOMOLE is described. CHARMM provides an extensive set of simulation algorithms, like molecular dynamics (MD) and free energy perturbation, and support for mature nonpolarizable and Drude polarizable force fields. TURBOMOLE provides fast QM calculations using density functional theory or wave function methods and excited state properties. CHARMM-TURBOMOLE is well-suited for extended Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 117 publications
1
54
0
Order By: Relevance
“…The classical relaxation of the systems was carried out using NAMD2 . The quantum chemical calculations were performed using TURBOMOLE versions 6.5 and 6.6, and the QM/MM calculations were performed with CHARMM/TURBOMOLE . Visual Molecular Dynamics (VMD) was used for analysis of the results, and electrostatic potentials at T= 298 K were calculated by solving the linearized Poisson–Boltzmann Equation using APBS …”
Section: Methodsmentioning
confidence: 99%
“…The classical relaxation of the systems was carried out using NAMD2 . The quantum chemical calculations were performed using TURBOMOLE versions 6.5 and 6.6, and the QM/MM calculations were performed with CHARMM/TURBOMOLE . Visual Molecular Dynamics (VMD) was used for analysis of the results, and electrostatic potentials at T= 298 K were calculated by solving the linearized Poisson–Boltzmann Equation using APBS …”
Section: Methodsmentioning
confidence: 99%
“…The MM system comprised the Nuo12/13/14 subunits and surrounding lipids and water molecules, with a total system size of approximately 75,000 atoms. The QM/MM MD simulations were simulated for 5 ps each, using a 1-fs integration time step, and a temperature of T = 310 K. The simulations were performed using the CHARMM/TURBOMOLE interface (71)(72)(73). Proton transfer from Lys-235 13 to Glu-377 13 .…”
Section: Qm/mm MD Simulationsmentioning
confidence: 99%
“…We have applied the established calculation software named NAMD package 52) with the CHARMM 22 [53][54][55][56] for simulating molecular interaction between A1 domain of VWF and N-terminus domain of GPIb . By Monte-Carlo simulation, we have previously shown that the localization GPIb is a key determinant factor for platelet binding with large size of VWF molecule 57) .…”
Section: Lrr5mentioning
confidence: 99%